2005
DOI: 10.1113/jphysiol.2005.090076
|View full text |Cite
|
Sign up to set email alerts
|

Balance between cardiac output and sympathetic nerve activity in resting humans: role in arterial pressure regulation

Abstract: Large, reproducible interindividual differences exist in resting sympathetic nerve activity among normotensive humans with similar arterial pressures, resulting in a lack of correlation between muscle sympathetic nerve activity (MSNA) and arterial pressure among individuals. Although it is known that the arterial pressure is the main short-term determinant of MSNA in humans via the arterial baroreflex, the lack of correlation among individuals suggests that the level of arterial pressure is not the only import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
249
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(272 citation statements)
references
References 29 publications
18
249
3
2
Order By: Relevance
“…Individuals with an upper body fat distribution pattern demonstrate a lower cardiac output and higher systemic vascular resistance compared with individuals with a lower body fat distribution pattern (Jern, 1992). These observations are consistent with recent findings by Charkoudian et al (Charkoudian et al, 2005) which suggest that there is balance between cardiac output and MSNA among healthy, normotensive individuals. Those individuals with a lower cardiac output exhibit higher levels of MSNA at rest.…”
Section: Potential Consequences Of Sympathetic Nervous System Activatsupporting
confidence: 83%
“…Individuals with an upper body fat distribution pattern demonstrate a lower cardiac output and higher systemic vascular resistance compared with individuals with a lower body fat distribution pattern (Jern, 1992). These observations are consistent with recent findings by Charkoudian et al (Charkoudian et al, 2005) which suggest that there is balance between cardiac output and MSNA among healthy, normotensive individuals. Those individuals with a lower cardiac output exhibit higher levels of MSNA at rest.…”
Section: Potential Consequences Of Sympathetic Nervous System Activatsupporting
confidence: 83%
“…Baroreceptor activation underlies repeated inhibition of muscle sympathetic nerve activity occurring during each cardiac cycle (32). Importantly, cardiac output provides a superior between-subject index of baroreceptor activation, which may be independent of systolic blood pressure differences (33). Our findings extend neuroimaging observations of central baroreflex responses (16,27) to show a direct modulation of cortical activity by afferent baroreceptor information within each cardiac cycle.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies in heart failure patients show that sympathetic hyperactivity is triggered by lower BRS 33, 34, 35. We observed that spontaneous BRS is decreased either BRS+ or BRS− in patients with RCM.…”
Section: Discussionsupporting
confidence: 49%